The Existence of Kampoeng Batik Jetis and its Impact on The Socio Economic Life of The People of Jetis Village Sidoarjo - Anggraini, Elisah Fitri; Indayani, Lilik; Sudarso, Satrio (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2024)
Kampoeng Batik Jetis Sidoarjo is the center of the handmade batik industry in Sidoarjo city. The purpose of this study was to determine the existence of Kampoeng Batik Jetis and its impact on the socio-economic life of the Jetis Sidoarjo community. Approach This research method uses descriptive qualitative methods so that data collection techniques are carried out by means of observation, interviews, and documentation. Data analysis techniques used in this study using 3 stages including data reduction, data presentation, and conclusion drawing. The results showed that most batik craftsmen use personal capital to run this batik business. The development of the batik industry in Kampoeng Batik Jetis from year to year is quite stable despite the many ups and downs in market share but the craftsmen still maintain their existence. The existence of the Kampoeng Batik Jetis industrial center has a positive impact in social and economic terms for the surrounding community. In social terms, for example, the development of tourism and increased awareness and welfare of the community. In terms of economy, it has an impact on employment, business opportunities, and encourages the growth of other sectors such as trade and services.